Type of menopause, age of menopause and cardiovascular disease: a cross-sectional study based on data from Rafsanjan cohort study - Zahra Jamali; Parvin Khalili; Fatemeh Ayoobi; Hajar Vatankhah; Ali Esmaeili-Nadimi; Faezeh Esmaeili Ranjbar; Mahboubeh Vatanparast (BMC, 2024)
Abstract Background Cardiovascular disease is the leading cause of death among women, but sex-specific risk factors are incompletely understood. In this study, we aimed to assess the associations between the type of menopause, and age at natural menopause with the odds of cardiovascular disease (CVD), and coronary heart disease (CHD). Methods This cross-sectional study is a part of data from the Rafsanjan Cohort Study (RCS) which is a branch of the Prospective Epidemiological Research Studies in Iran (PERSIAN). A sample of 1767 postmenopausal women were included. The diagnosis for CVD and CHD was based on self-report questionnaires. Menopause age was categorized as < 40, 40-44, 45-49, and ≥ 50. Also, the menopause types were classified as natural and induced menopause (surgery or chemotherapy). The association was evaluated by logistic regressions. Results The menopause age < 40 years had higher odds of CVD compared to women with menopause age > 40 years (OR: 2.66; 95%CI 1.29-5.48). Women with induced menopause had higher odds of CVD compared to women with natural menopause (OR = 1.44, 95% CI 1.04-1.98). In terms of the odds of CHD, the results showed that the odds of CHD increased in menopause age < 40 years and induced menopause compared to reference groups (OR: 2.49, 95% CI 1.15-5.37, OR = 1.48; 95% CI 1.06-2.07, respectively). Conclusion Premature menopause and induced menopause should be considered as important risk factors for CVD, and CHD. Health policymakers should pay more attention to the type of menopause and the age of menopause in postmenopausal women to predict the risk of CVD and preventive strategies.